PENGARUH BUZZ MARKETING, PRICE, PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK LIP TINT JOLLY TINT PINKROULETTE DI KALANGAN MAHASISWA - Hasna Rafifa; Veni Rafida (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to analyze the influence of buzz marketing, price, and perceived quality on the purchasing decisions of Jolly Tint Pinkroulette Lip Tint products among Surabaya University students. Primary data was obtained through a survey using questionnaires distributed to 400 respondents who are students in Surabaya. Data analysis was conducted using a descriptive quantitative approach employing the multiple linear regression method. The research findings indicate that buzz marketing, price, and perceived quality simultaneously have a significant influence on the purchasing decisions of Jolly Tint Pinkroulette Lip Tint products. The practical implications of this research emphasize the importance for companies to consider buzz marketing strategies, competitive pricing, and product quality enhancement to influence consumer purchasing decisions. This study is expected to contribute to understanding consumer behavior in the digital era and serve as a reference for companies in designing effective marketing strategies.